Assessment of peri-implant bone stress distribution with the effect of attachment type and implant location using finite element analysis - Shima Aalaei; Atefeh Sheikhi; Parisa Mehdian; Farnoosh Taghavi; Sara Salimian; Farnaz Taghavi-Damghani (Tabriz University of Medical Sciences, 2023)
Background. The objective of the current research was to evaluate how stress is distributed in the peri-implant bone of a mandibular overdenture with implants placed asymmetrically to the midline. Methods. A 26-year-old male's mandible, with missing teeth, was examined using computed tomography (CT) scanning. Two implants were inserted at right angles to the occlusal plane, in the positions of the right canine and left lateral incisor of the mandible, with an internal connection. Two types of attachments (bar and ball) were designed. To simulate the clinical condition, anterior (on central incisors) and bilateral posterior (on premolars and molars) loadings were applied. The stress distribution was assessed using finite element analysis (FEA). Results. The lateral incisor level implant was found to have the highest maximum principal stress (about 33 MPa) in both models in the anterior loading condition. However, in both models, the canine-level implant revealed more stress values (about 22 MPa) in the posterior loading condition. Conclusion. In mandibular implant-supported overdentures, when implants were placed asymmetrically to the midline, one acted as a fulcrum and sustained more occlusal load. The bar attachment system did not reveal superior results in terms of stress distribution compared to the ball attachment.